A Tuned Alternating D–A Copolymer Hole‐Transport Layer Enables Colloidal Quantum Dot Solar Cells with Superior Fill Factor and Efficiency. Issue 48 (28th October 2020) - Kim, Hong Il; Baek, Se‐Woong; Cheon, Hyung Jin; Ryu, Seung Un; Lee, Seungjin; Choi, Min‐Jae; Choi, Kyoungwon; Biondi, Margherita; Hoogland, Sjoerd; de Arquer, F. P. García; Kwon, Soon‐Ki; Kim, Yun‐Hi; et al.
Abstract: The need for optoelectronic and chemical compatibility between the layers in colloidal quantum dot (CQD) photovoltaic devices remains a bottleneck in further increasing performance. Conjugated polymers are promising candidates as new hole‐transport layer (HTL) materials in CQD solar cells (CQD‐SCs) owing to the highly tunable optoelectronic properties and compatible chemistries. A diketopyrrolopyrrole‐based polymer with benzothiadiazole derivatives (PD2FCT‐29DPP) as an HTL in these devices is reported. The energy level, molecular orientation, and hole mobility of this HTL are manipulated through molecular engineering. By levering the polymer's optical absorption spectrum complementary to that of the CQD active layer, EQE across the visible and near‐infrared regions is maximized. As a result, a PD2FCT‐29DPP‐based device exhibits a fill factor of 70% and approximately 35% efficiency enhancement compared to a PTB7‐based device. Abstract : A new DPP‐based alternating D–A copolymer (PD2FCT‐29DPP) is developed for use as a hole‐transport layer. PD2FCT‐29DPP addresses the different requirements for an HTL, offering favorable energetics, near‐infrared absorption, and efficient charge transfer. Therefore, a PD2FCT‐29DPP‐based device achieves a remarkable FF of 70% and the highest PCE of 14.0% among PbS CQD‐SCs.